THEACHER STRATEGIES FOR ENHANCHING STUDENT LEARNING MOTIVATION IN EARLY GRADE MATHEMATICS AT SD ISLAM SABILILLAH CUKIR. - Eka Putri, Aulia; zahrani susilo , claudya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to investigate and describe the pedagogical strategies employed by teachers to enhance students' learning motivation in mathematics within the lower-grade classes of SD Islam Sabilillah Cukir. The primary problem addressed in this research is the common perception among early-grade students that mathematics is a difficult and intimidating subject, which often leads to low engagement, anxiety, and a lack of interest in numerical concepts. To address this issue, a qualitative research methodology with a case study approach was utilized. Data were collected through structured observations, semi-structured interviews with classroom teachers, and extensive documentation of learning activities. The results of the research indicate that teachers implement a multifaceted strategy involving the use of concrete manipulative media, the integration of Islamic values into mathematical contexts, and a consistent reward-and-praise system to build students' confidence. Furthermore, the findings reveal that creating a joyful learning atmosphere through "ice-breaking" activities and game-based learning significantly reduces students' math anxiety and fosters a proactive learning attitude. These strategies not only improve students' focus during lessons but also build a strong foundational interest in mathematics. In conclusion, the teacher's role as a creative facilitator is crucial in transforming abstract mathematical concepts into relatable, enjoyable, and motivating experiences for lower-grade students at SD Islam Sabilillah Cukir.